Triazophos (TAP) removal in horizontal subsurface flow constructed wetlands (HSCWs) and its accumulation in plants and substrates - Juan Wu (Nature Portfolio, 2017)
Abstract Triazophos (TAP) is a widely used phosphorus pesticide in China that possesses a potential risk for water pollution. We have studied the removal efficiency of TAP using pilot-scale horizontal subsurface flow constructed wetlands (HSCWs) as well as the contribution of plants, substrates and other pathways to its removal. For TAP concentrations of 0.12 ± 0.04 mg L−1, 0.79 ± 0.29 mg L−1 and 3.96 ± 1.17 mg L−1, the removal efficiencies were 94.2 ± 3.7%, 97.8 ± 2.9% and 84.0 ± 13.5%, respectively, at a hydraulic loading rate (HLR) of 100 mm d−1; at an HLR of 200 mm d−1, the removal efficiencies were 96.7 ± 1.3%, 96.2 ± 1.7% and 61.7 ± 11.1%, respectively. The isopleth maps of TAP along the direction of flow indicate that most of the TAP removal occurred in the front and middle regions, while the major removal region would move forward with increasing influent TAP. Plant and substrate accumulation accounted for 0.035 ± 0.034% and 4.33 ± 0.43% of the total removal, respectively, indicating that over 95% of the TAP removal was achieved through other mechanisms. Thus, these results suggest HSCWs can be an effective approach with which to treat TAP contaminated water. Furthermore, the longitudinal scale and hydraulic conditions, as well as the roles of plants, substrates and microbes and their interactions, should be further considered in the design and application of CWs for pesticide pollution control.